Le Goff, History And Memory - Frey, Linda (Teaching History: A Journal of Methods, 1993)
According to the Greeks, the goddess Mnemosyne, the personification of memory, gave birth to the muses after sleeping with Zeus. Jacques Le Goff explores the relationship between the goddess and one of her muse offspring, Clio, in this thought-provoking work on the historian's craft. A leading member of the Annales school, Jacques Le Goff demonstrates the tools of the school that has so revolutionized historical studies. Steven Randall and Elizabeth Claman have selected and translated four of ten articles that appeared a decade ago in Italian translation in the Enciclopedia and later separately as Storia e Memoria. These texts focus on Past/Present, Antique/Modern, Memory, and History.